Pengembangan dan Evaluasi Kurikulum Pendidikan Di Pondok Pesantren Desa Ganjaran Gondanglegi Malang - Yazidul Busthomi; Syamsul A’dlom (Jurnal Pendidikan Islam, 2019)
Abstract: Islamic boarding schools in the village of Malang Ganjara n Gondanglegi are Islamic educational institutions with a Salaf Islamic curriculum so far believed to be a place of religious education, proven to be one of the places where preaching education still exists. However, curriculum development and evaluation i n this Islamic boarding school, there is still no data that can be ascertained, so it is interesting to study. So the researcher raised a title "development and evaluation of educational curricula in Malang Ganjaran Gondanglegi boarding school". Based on t he background of the problem stated above, the problem formulation can be taken, namely: 1) How is the development of the Islamic religious education curriculum in the Islamic boarding school of Ganjaran Gondanglegi village in Malang ?. 2) What is the eval uation of the Islamic religious education curriculum in the Islamic boarding school of Ganjaran Gondanglegi village in Malang ?. This study uses a qualitative approach. Data was collected through interviews, participant observation and documentation. From the results of this study it was found that the development of the Islamic religious education curriculum in the Ganjaran village Islamic boarding school is by developing a curriculum plan with clear objectives, developing curriculum plans according to the characteristics of the santri, preparing the lesson schedule, determining the teaching materials to be taught, determining the material that must be read by santri, provide a source of teaching and learning processes, prepare prospective Islamic religious education teachers, and in the application of educational curriculum is strongly influenced by the ability of the teacher. The evaluation of the Islamic religious curriculum in the Ganjaran village boarding school was carried out twice in the development of its curriculum, using measurement instruments in the form of standard tests, teacher - made tests, oral tests, and questionnaires.